NEK4 suppresses cell proliferation in BT20 triple-negative breast cancer cells by diminishing expression of cell cycle genes, while its depletion mitigates proliferation in other cell lines - Joshi, Rashmi R.; Sepulveda, E. Gloria; Lujan, F. Ester; DeVargas, Jacob M.; Ashley, Amanda K. (Frontiers in Oncology, 2025)
Never In Mitosis Gene A (NIMA)-related kinase 4 (NEK4), a serine/threonine protein kinase, is involved in several cellular processes, including the DNA damage response and mRNA splicing, and we identified it as a potential new drug target in triple-negative breast cancer. We observed via live-cell imaging that multiple NEK4-depleted cell lines proliferated more slowly than control cells, except the BT20 and MCF12A cell lines, in which proliferation was stimulated with NEK4 depletion. We hypothesized that NEK4 regulates genes involved in cell proliferation in BT20 cells. NEK4-depleted BT20 cells were subjected to RNA-seq. Enrichment analysis revealed the upregulation of genes involved in cell cycle, mitosis, and G protein-coupled receptor (GPCR) ligand binding and the downregulation of genes involved in mRNA splicing, consistent with previous reports. We used the STRING database to select a subset of cell cycle genes that were upregulated in NEK4-depleted cells. We assessed cell cycle distribution and found a decrease in the percentage of cells in G0/G1 and an increase in G2/M, suggesting an enhanced proliferative phenotype in BT20 cells. NEK4 depletion did not consistently alter the expression of p21, a putative target of NEK4, in the multiple cell lines examined. We explored the role of NEK4 in DNA repair and observed that NEK4 depletion did not impact basal DNA damage levels but did decrease γH2AX foci following exposure to etoposide. Our data indicate that NEK4 depletion differentially alters cell proliferation in varying cell lines, most likely by altering cell cycle regulation. Understanding its role in cell cycle regulation could be valuable in developing therapeutic strategies and patient stratification, as we and others have identified NEK4 as a potential target for new drug development in triple-negative breast cancer.